Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4103/0972-0707.120934
|View full text |Cite
|
Sign up to set email alerts
|

Management of a large periapical lesion using BiodentineTMas retrograde restoration with eighteen months evident follow up

Abstract: Injury to anterior teeth is a common event. It requires a treatment approach that assures the complete biologic healing and functional restoration of the tooth or teeth involved. A cystic lesion, which is unable to heal nonsurgically, heals well with surgical intervention and use of mineral trioxide aggregate (MTA) as retrograde filling has been reported in literature. Another material with largely improved handling properties; Biodentine™ (Septodont, St. Maurdes Fossés, France) was introduced in 2011. It is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 7 publications
0
29
0
2
Order By: Relevance
“…This material was also used as pulp capping material and as reparative material in perforations, internal/external resorptions, apexifications and retrograde fillings (5). Thus, this material exhibited adequate resistance to be placed in regions where mechanical strength is required, like underneath final restorative procedures (6).…”
Section: Introductionmentioning
confidence: 99%
“…This material was also used as pulp capping material and as reparative material in perforations, internal/external resorptions, apexifications and retrograde fillings (5). Thus, this material exhibited adequate resistance to be placed in regions where mechanical strength is required, like underneath final restorative procedures (6).…”
Section: Introductionmentioning
confidence: 99%
“…The periapical modality for managing failure of conventional orthograde endodontic treatment in case of a large non healing periapical lesion is apical surgery with success rate 86-92%. [2] Kolkate and Pawar conducted a study that compared microleakage of GIC , MTA and Biodentine when used as a retrograde filling material and concluded that Biodentine exhibited the least microleakage. [2] Biodentine powder contains tricalcium silicate, calcium carbonate and dicalcium silicate, zirconium oxide and liquid consist of calcium carbonate in aqueous solution with an admixture of polycarbonate.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Kolkate and Pawar conducted a study that compared microleakage of GIC , MTA and Biodentine when used as a retrograde filling material and concluded that Biodentine exhibited the least microleakage. [2] Biodentine powder contains tricalcium silicate, calcium carbonate and dicalcium silicate, zirconium oxide and liquid consist of calcium carbonate in aqueous solution with an admixture of polycarbonate. It possess better physical and biological properties in comparison to other tricalcium silicate based cements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This material has shown promising results with respect to its biocompatibility, mechanical properties, handling characteristics, sealing ability and bioactivity. 10,11 Biodentine with its shorter setting time and potential for increased calcium (Ca) and silicate (Si) uptake in the adjacent root canal dentin similar to MTA would ensure the a monoblock effect with the achievement of an early fluid tight seal. 12 When restoring root canal treated tooth, especially when the remaining root dentine is thin, it is preferable to opt for that radicular post having elastic modulus similar to that of dentin.…”
Section: Discussionmentioning
confidence: 99%